Exploring Students’ Speaking Anxiety and Its Impact on Oral Performance in an Extensive Speaking Class - Wahyuni, Ika Yuli (Har Press Indonesia, 2025)
This study explores students’ speaking anxiety and its impact on their oral performance in an Extensive Speaking class. The research was motivated by the observation that many English as a Foreign Language (EFL) learners experience nervousness, fear of making mistakes, and lack of confidence when speaking English, which can hinder their fluency and classroom participation. The study aimed to identify the sources of speaking anxiety, its effects on oral performance, and the coping strategies used by students to manage it. The research employed a qualitative design using a semi-structured interview with open-ended questions, distributed through Google Forms due to the online implementation of the Extensive Speaking course. The participants consisted of eight students selected through purposive sampling, representing different English proficiency levels based on the Common European Framework of Reference (CEFR): two students each from levels A1, A2, B1, and B2. The data were analyzed thematically following Braun and Clarke’s (2006) six-phase framework. Thematic analysis revealed four major themes: (1) Emotional and Physical Manifestations of Speaking Anxiety, where students experienced nervousness, shaking, and mind blank during speaking tasks; (2) Sources of Anxiety: Fear of Evaluation and Linguistic Insecurity, in which fear of making mistakes and peer judgment were dominant causes; (3) Impact of Anxiety on Oral Performance, showing that anxiety disrupted fluency, pronunciation, and confidence; and (4) Coping Strategies and Pedagogical Support, where students reported using self-preparation, relaxation, and support from lecturers as effective means to reduce anxiety. The findings indicate that speaking anxiety is a common psychological barrier across all proficiency levels, though its intensity and control vary by level. Creating a supportive, low-pressure classroom environment and incorporating confidence-building activities are essential in helping students manage anxiety and enhance oral performance.